The realistic trend in the productions of students of the Institute of Fine Arts (Al-Academy, 2024)
The aim of the research is to uncover the realistic trend that formed one of the schools of art, which appeared in the drawings of fine arts students. The importance lies in shedding light on one of the trends of modern art that conveys the social life aspect of people’s daily lives by recording reality to convey the artist’s message, which expresses the ideas and perceptions of contemporary times.The descriptive analytical approach was followed and (3) paintings were chosen as the research sample from the products of students in the fifth stage of the Department of Fine Arts, which represented the realistic trend and were analyzed according to what the research emerged from the indicators of the theoretical framework and previous studies and concluded with the following results: The art student recorded social life and heritage in realistic and traditional details as a result of his influence by the social and cultural situation that the student lives and daily life, in addition to his influence by the environmental aspect of public life